CRITICS ABOUT THE POST-MARXIST AMBIVALENCE - Morera Herrera, David (2013)
The author discusses a number of concepts and tenets of what is generically called the post-Marxist current, which self-identifies as contestatory, and that extends particularly in the nineties of the twentieth century. This post-Marxist approach aims to review, dilute or overcome some axes of Marxist paradigm, primarily the centrality of social classes in the contemporary world and the class struggle as an engine of social change. In that context, this approach appropriates and builds his theories based on new and not so new categories such as globalization, civil society and citizenship, giving them different contents. The author attempts to identify to what responds this intellectual movement, what are its achievements and constraints, also, he faces it, trying to claim the radical essence of Marxist thought..